Bi-allelic Variants in METTL5 Cause Autosomal-Recessive Intellectual Disability and Microcephaly - Richard, Elodie M.; Polla, Daniel L.; Assir, Muhammad Zaman; Contreras, Minerva; Shahzad, Mohsin; Khan, Asma A.; Razzaq, Attia; Akram, Javed; Tarar, Moazzam N.; Blanpied, Thomas A.; Ahmed, Zubair M.; Abou Jamra, Rami; et al. (American Journal of Human Genetics, 2019)
Intellectual disability (ID) is a genetically and clinically heterogeneous disorder, characterized by limited cognitive abilities and impaired adaptive behaviors. In recent years, exome sequencing (ES) has been instrumental in deciphering the genetic etiology of ID. Here, through ES of a large cohort of individuals with ID, we identified two bi-allelic frameshift variants in METTL5, c.344_345delGA (p.Arg115Asnfs∗19) and c.571_572delAA (p.Lys191Valfs∗10), in families of Pakistani and Yemenite origin. Both of these variants were segregating with moderate to severe ID, microcephaly, and various facial dysmorphisms, in an autosomal-recessive fashion. METTL5 is a member of the methyltransferase-like protein family, which encompasses proteins with a seven-beta-strand methyltransferase domain. We found METTL5 expression in various substructures of rodent and human brains and METTL5 protein to be enriched in the nucleus and synapses of the hippocampal neurons. Functional studies of these truncating variants in transiently transfected orthologous cells and cultured hippocampal rat neurons revealed no effect on the localization of METTL5 but alter its level of expression. Our in silico analysis and 3D modeling simulation predict disruption of METTL5 function by both variants. Finally, mettl5 knockdown in zebrafish resulted in microcephaly, recapitulating the human phenotype. This study provides evidence that biallelic variants in METTL5 cause ID and microcephaly in humans and highlights the essential role of METTL5 in brain development and neuronal function.
CRIS-Team Scopus Importer:2019-10-08
Keywords: autosomal recessive intellectual disability; facial dysmorphism; intellectual disability; m6A methyltransferase; METTL5; microcephaly; zebrafish